Green Mediated Synthesis of MgO Nano-Flakes and Its Electro-Chemical Applications. (2018) - Arun Kumar, N.B.; Mahendra, B.; Sirajudeeen, J; Anil Kumar, M.R.; Nagaswarupa, H.P.; Ravi Kumar, C.R.; Umesh, B.
Abstract: MgO nano flakes were synthesized by a green mediated route using Vetiver (Chrysopogonzizanioides) grass as a fuel. The obtained products were characterized by powder X-ray diffraction (PXRD), diffuse reflectance spectroscopy (DRS) Scanning electron microscope (SEM), Travelling Electron Microscope (TEM) and Fourier transform infrared spectroscopy (FTIR). PXRD patterns show singlecubic phase MgO matched with JCPDS card No. 4-829 with the crystallite size was found to be ∼ 20-25 nm. SEM result reveals flakes and agglomerated nanoparticles. The optical energy gap was 4.50eV which demonstrates that there is a movement to the higher wavelengths of the absorption edge with reduction of the energy gap when using green fuel for synthesis.The electrochemical properties of MgO havebeen investigated using cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) measurements using a modified carbon paste electrode. Further, modified carbon paste electrodeis also found to exhibit higher capacitance and lower charge transfer resistance. These findings suggest that the synthesized electrode possess better electrochemical properties and thus can be recognized as apromising candidate for the battery electrode applications